Ironing out the Wrinkles: Technological and Aesthetic Change in Domestic Irons, 1880-1920 - Gann, Emily (Scientia Canadensis)

(untitled) (CSTHA/AHSTC, 2013)
In 1914, James Smart Manufacturing Company advertised the sale of two technologically identical, yet stylistically different irons: one had a black painted finish, the other, a nickel plated finish. Both styles operated in the same fashion, producing a comparable final product, however the latter was a new addition to the catalogue and was set at a higher price. The similar functionality of these domestic tools suggests that this stylistic change was made on behalf of clients’ preference and taste, rather than quality of work. By employing an object based analysis to the iron, this paper will illustrate the reciprocal relationship between gender and technology and engage with the growing discourse surrounding the changes in domestic space from 1880 to 1920 in Canada.